Measurement of Physical Activity Level in Patients with Ankle Osteoarthritis. Issue 4 (22nd October 2020) - Kimura, Seiji; Yamaguchi, Satoshi; Ono, Yoshimasa
Category: Ankle Arthritis Introduction/Purpose: Maintaining physical activity (PA) is important for reducing the risk of lifestyle-related diseases and fundamental to keep healthy. PA is reduced in patients with knee and hip osteoarthritis, but PA of patients with ankle osteoarthritis has not been clarified. The purpose of this research is to compare PA level and proportion of patients who meet recommendations for health between ankle osteoarthritis and control patients. Methods: The subjects were 50 patients with ankle osteoarthritis (OA group), and 50 patients with minor hand disease matched by age and gender (control Group), who visited our outpatient clinic from October 2016 to April 2019. Both groups had 16 men and 34 women, with an average age of 68 years for the OA group and 66 years for the control group. The visual analogue scale for foot pain was 5.5 on average in the OA group and 0.3 in the control group. The physical activity for one week was measured using a tri-axial accelerometer. Unpaired t-tests were used to compare the number of steps per day and moderate or higher activity time between the OA group and the control group. The proportions of the OA group and the control group that met the recommendations set by Japan and the World Health Organization were compared using Fisher's exact test. Results: The number of steps per day was 4177 +- 2312 steps in the OA group and 6802 +- 2851 steps in the control group, which was significantly lower in the OA group (p <0.001). Moderate PA time was 448 +- 232 minutes in the OA group and 634 +- 336 minutes in the control group, OA group was significantly lower (p = 0.02). Vigorous PA time was no difference between the two groups. The WHO recommendations were met by 45 patients in the OA group and 48 in the control group, no difference. The Japanese criterion were met by 33 patients in the OA group and 46 in the control group, which was significantly lower in the OA group (p = 0.001). Conclusion: PA of patients with ankle osteoarthritis was less than control patients. The proportion of patients meeting recommendations for health was lower in the OA group than the control group.